Employment effects of low-skilled immigrants in Korea - Jungho Kim (Institute for the Study of Labor (IZA), 2013)
This study examines the impact of inflows of foreign workers on Korean natives' economic performance - namely, employment - through the Employment Permit System, the basis of Korea's system by which to introduce low-skilled immigrants. Using National Employment Insurance data, analyses reveal that the adjustment cost related to the introduction of foreign workers was not substantial over the 2004-2005 period. However, a substitution effect exists between the employment of foreign and native workers in the service industry and among less-educated natives. The results suggest that policy assistance is needed to lessen the impacts caused by inflows of foreign workers and to enhance adjustments within the labor market on a sector-by-sector basis.
Keywords: F22; J61; J63; 330; employment permit system; low-skilled immigrants; employment of natives; adjustment costs